Differential in vitro and in vivo anti-angiogenic activities of acetal and ketal andrographolide derivatives in HUVEC and zebrafish models. Issue 105 (31st October 2016) - Sheng, Dekuan; Li, Jingjing; Wang, Kun; Peng, Yuran; Li, Shang; Sun, Yicheng; Liu, Zhuyun; Wang, Decai; Lee, Simon Ming Yuen; Zhou, Guo-Chun
Abstract : Acetal and ketal andrographolide derivatives presented differing anti-angiogenic activities when applied to in vitro and in vivo models, leading to different inhibitory outcomes. Abstract : A series of acetal and ketal derivatives of andrographolide were synthesized and their anti-angiogenic activities were tested in vitro and in vivo using HUVEC and zebrafish models, respectively. These compounds exhibited better angiogenesis inhibitory activity in both models than the parent compound andrographolide (1 ). The compounds' SARs differed for the HUVEC and zebrafish models, in that 14α-ketal2 showed the best activity for in vivo anti-angiogenesis in zebrafish while 14α-acetals4, 5 and6 had greater in vitro anti-angiogenic activity with HUVECs than the other compounds and1 . The results suggested that methylene acetals4, 5 and6 were possibly hydrolyzed into3 or1 in zebrafish and that 14α-ketal2 probably did not fully act as a pro-drug of3 or1 in zebrafish, instead exerting the anti-angiogenic effect itself or being metabolized into an unknown more active form(s) than3 and1 to block in vivo angiogenesis in zebrafish. The underlying molecular mechanisms of compound2 's action were explored and the results indicated that VEGF-stimulated angiogenesis was significantly inhibited by compound2 via targeting the phosphorylation of VEGFR2 and VEGFR2-mediated downstream angiogenesis signaling pathways. Therefore, this report demonstrates that andrographolide derivative(s) can be developed into therapeutic agent(s) against excessive angiogenesis, including tumor angiogenesis, after further improvement of the potency and stability of this series of andrographolide derivatives.